2022
DOI: 10.1111/mpp.13234
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for improving watermelon resistance to cucumber green mottle mosaic virus by exogenous boron application

Abstract: The molecular mode controlling cucumber green mottle mosaic virus (CGMMV)‐induced watermelon blood flesh disease (WBFD) is largely unknown. In this study, we have found that application of exogenous boron suppressed CGMMV infection in watermelon fruit and alleviated WBFD symptoms. Our transcriptome analysis showed that the most up‐regulated differentially expressed genes (DEGs) were associated with polyamine and auxin biosynthesis, abscisic acid catabolism, defence‐related pathways, cell wall modification, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
(114 reference statements)
4
10
0
Order By: Relevance
“…Here, we measured the concentrations of 10 essential nutrient elements (N, P, K, Ca, Mg, S, Fe, Zn, Cu, and B) and expressions of main genes related to nutrient element absorption and transport in watermelon leaves and fruits from different treatments (Figure ). In this study, the results of these nutrient element contents were similar or consistent with those in previous reports. The contents of most nutrient elements and the expressions of their absorption and transport genes (i.e., NIP2;1 , NIP5;1 , BOR2 , NRT1.5 , KUP11 , and VIT1 ) were strongly associated with B treatment and/or CGMMV infection in watermelon leaves and fruits (Figure , Tables S3 and S4), which demonstrated that the nutrient element homeostasis in watermelon was indeed affected by B element and CGMMV infection.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Here, we measured the concentrations of 10 essential nutrient elements (N, P, K, Ca, Mg, S, Fe, Zn, Cu, and B) and expressions of main genes related to nutrient element absorption and transport in watermelon leaves and fruits from different treatments (Figure ). In this study, the results of these nutrient element contents were similar or consistent with those in previous reports. The contents of most nutrient elements and the expressions of their absorption and transport genes (i.e., NIP2;1 , NIP5;1 , BOR2 , NRT1.5 , KUP11 , and VIT1 ) were strongly associated with B treatment and/or CGMMV infection in watermelon leaves and fruits (Figure , Tables S3 and S4), which demonstrated that the nutrient element homeostasis in watermelon was indeed affected by B element and CGMMV infection.…”
Section: Discussionsupporting
confidence: 91%
“…In watermelon fruits, genes related to cell wall biosynthesis (i.e., API , CSLD3 , CESA4 , COBRA ) and cell wall modification (i.e., XTHs , PE/PEIs , and EXLA1 ) were upregulated, and wall catabolism-associated genes (i.e., BG12 and Pel13 ) were downregulated by B-application under CGMMV stress, which were consistent with the expressions of cell wall biosynthesis genes ( CesA and COBL7 ) and pectin degradation genes ( PG and PL1 ) in watermelon fruits by four treatments (Figure C). In addition, silencing XTH23 and PE/PEI7 caused more severe WBFD with lower levels of lignin, cellulose, hemicellulose, soluble pectin, and propectin in watermelon flesh . In this study, watermelon fruits in the C + H group were severely infected by CGMMV, and the contents of lignin, cellulose, hemicellulose, and pectin were also decreased (Figure B).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations